AKTIVITAS ANTIOKSIDAN DARI EKSTRAK KULIT NANAS (ANANAS COMOSUS (L) MERR) - Hatam, Sri Febriani; Suryanto, Edi; Abidjulu, Jemmy (PHARMACON, 2013)
ABSTRACT The objectives of this research were to determine antioxidant n activity from pineapple peal extract. Pineapple peel extracted by maceration, soxhlet and reflux using ethanol 80% as a solvent. Phenolics and flavonoids content of Crude extract were analyzed.Evaluation of antioxidant activity using DPPH free radicals method, The results shows that maceration, soxhlet and reflux extract possess phenolics content 16,53; 28,78; 16,02 g/mL respectively, and  flavonoid total content 3,514; 5,115; 4,414 g/mL respectively. Maceration extract with concentration 3000 g/mL possess low free radical scavenging activity, and soxhlet extract possess the highest.Inhibition concentration 50% (IC50) of soxhlet extract were 602,56 g/mL, it?s indicate that soxhlet extract possess high scavenging of 50% free radicals. This result shows that pineapple peel extract possess phytochemical phenolics and flavonoids that potential to be antioxidant and as active compound of sun screen. Keywords: antioxidant, pineapple peel extract.